Lektura deiktyczna. Rozważania o dyskursie miłości oraz poetyce interpretacji - Mastalski, Arkadiusz Sylwester (Wydawnictwo Naukowe UAM, 2014)
This article analyzes confessions of love from the perspective of communication – it shows the paradoxical character of such confessions and the disparity between this and other models of communication. By referring to the writings of Roland Barthes, Ludwig Wittgenstein, and Jacques Derrida as well as papers dealing with cognitive linguistics and cognitive poetics, the article presents the interpretative consequences of deictic shifts (shifts in textual perspectives).
Deictic reading: reflections on the discourse of love and the poetics of interpretation